Red Dry Wine Modulates Plasma Cholesterol Levels and Cardiac Enzymes in Humans - Rogério Corrêa Peres; Rafael Hirata; Samuel Rangel Claudio; Taina Liz; Tamires Corrêa da Silva; Daniel Araki Ribeiro (Journal of Pharmacy and Nutrition Sciences, 2012)
Several studies has pointed that red wine diet, rich in polyphenols, has several effects like vasodilation, possible antioxidant effect, decrease of cellular events of atherosclerosis, decrease of blood pressure, and reduction of cardiovascular risks. This paper proposes an investigation of the effects of a 21 days diet of 200 ml dialy of red dry wine for markers of muscle injury such as CK and CK-MB, besides cholesterol and its fractions, LDL and HDL, and triglycerides, in normal subjects.The results showeddecreased levels of plasma total cholesterol and LDL, and a tendency to increased levels of HDL, what suggests red dry wine has effects on decrease cardiovascular risks. However, significant increase of cardiacCK-MB isoenzyme was observed what could point to increase the oxidation of muscle tissues. It can be concluded that, despite the CK-MB increase, red dry wine can be considered as a tool to decrease cardiovascular diseases risks.